Determination of glyoxal, methylglyoxal, and diacetyl in red ginseng products using dispersive liquid–liquid microextraction coupled with GC–MS. Issue 6 (7th February 2019) - Lee, Yun‐Yeol; Shibamoto, Takayuki; Ha, Sang‐Do; Ha, Jaeho; Lee, Jangho; Jang, Hae Won
Abstract: A simple and rapid dispersive liquid–liquid microextraction method coupled with gas chromatography and mass spectrometry was applied for the determination of glyoxal as quinoxaline, methylglyoxal as 2‐methylquinoxaline, and diacetyl as 2, 3‐dimethylquinoxaline in red ginseng products. The performance of the proposed method was evaluated under optimum extraction conditions (extraction solvent: chloroform 100 μL, disperser solvent: methanol 200 μL, derivatizing agent concentration: 5 g/L, reaction time: 1 h, and no addition of salt). The limit of detection and limit of quantitation were 1.30 and 4.33 μg/L for glyoxal, 1.86 and 6.20 μg/L for methylglyoxal, and 1.45 and 4.82 μg/L for diacetyl. The intra‐ and interday relative standard deviations were <4.95 and 5.80%, respectively. The relative recoveries were 92.4–103.9% in red ginseng concentrate and 99.4–110.7% in juice samples. Red ginseng concentrates were found to contain 191–4274 μg/kg of glyoxal, 1336–4798 μg/kg of methylglyoxal, and 0–830 μg/kg of diacetyl, whereas for red ginseng juices, the respective concentrations were 72–865, 69–3613, and 6–344 μg/L.